2018
DOI: 10.1111/iju.13838
|View full text |Cite
|
Sign up to set email alerts
|

Transperitoneal versus retroperitoneal laparoscopic adrenalectomy for large pheochromocytoma: Comparative outcomes

Abstract: Objectives To evaluate operative and oncological outcomes of laparoscopic adrenalectomy through a transperitoneal approach and retroperitoneal approach for large (>5 cm in diameter) pheochromocytomas. Methods We retrospectively compared the results of a transperitoneal approach with those of a retroperitoneal approach in 22 patients (mean age 57.5 years, range 38–76 years) with unilateral large pheochromocytomas (12 right, 10 left). The mean body mass index, operation time, pneumoperitoneum time, estimated blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
(68 reference statements)
0
26
0
Order By: Relevance
“…The incidence of large, 6-10 cm adrenal tumors is 8.6-38.6%, showing malignancy in a quarter of the cases [23]. Tumor size shows direct correlation with chances of malignancy, although size is not always a reliable predictive factor.…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of large, 6-10 cm adrenal tumors is 8.6-38.6%, showing malignancy in a quarter of the cases [23]. Tumor size shows direct correlation with chances of malignancy, although size is not always a reliable predictive factor.…”
Section: Discussionmentioning
confidence: 98%
“…7). Shiraishi et al reported a retrospective study that found that TLA had a higher incidence of hypertensive crisis than PRA (58% vs 40%, retrospectively) [19]. Wessel et al performed a retrospective, multicenter study that included 341 patients and found that the overall and cardiovascular morbidity rates were comparable between the two approaches [23].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies were included in our study [16][17][18][19]. The PRISMA flow diagram of the search process is summarized in Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…In this case, we chose the transperitoneal approach. Shiraishi et al . reported that the retroperitoneal approach is feasible, safer, and faster than the transperitoneal approach for large right‐sided adrenal pheochromocytomas because early transection of the feeding artery is beneficial to managing the tumor and reducing the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we chose the transperitoneal approach. Shiraishi et al 8 reported that the retroperitoneal approach is feasible, safer, and faster than the transperitoneal approach for large right-sided adrenal pheochromocytomas because early transection of the feeding artery is beneficial to managing the tumor and reducing the risk of bleeding. However, for paragangliomas such as those in our case, we choose the transperitoneal approach over the retroperitoneal approach because it can provide a wide operative space, preparations for open conversion can be simultaneously made during the surgical procedure, we can more easily recognize the anatomical relationship between the tumor and abdominal organs, and hand-assisted surgery is inappropriate when securing a wide operative space.…”
Section: Discussionmentioning
confidence: 99%